Species diversity, taxon structure and distribution of the Chlorophytes on Truong Sa archipelago - Tien, Dam Duc; Hang, Nguyen Thi Thu; Hue, Phan Thu; Lan, Tran Dinh (Vietnam Journal of Marine Science and Technology, 2020)
The results of research on characteristic of distribution and taxa structure of Chlorophytes (Chlorophyta) at nine islands of Truong Sa archipelago (Truong Sa, Da Tay, Thuyen Chai, Toc Tan, Sinh Ton, Nam Yet, Song Tu Tay, Da Nam and Son Ca) indicate that there are 67 species of Chlorophytes, they belong to 4 orders, 14 families and 22 genera. The number of species at the sampling islands ranged from 13 species/island (Toc Tan isd.) to 43 species/island (Nam Yet isd.) with the average of 25.5 species/island. Sorensen similarity coefficient at the sampling sections ranged from 0.24 (between Song Tu Tay and Thuyen Chai) to 0.74 (between Nam Yet and Song Tu Tay) with the average of 0.45. Among 67 species in nine islands, there are 10 species distributed only in the intertidal zone (they are occupying 14.9% of total species), 14 species (31.4%) in subtidal zone only and 43 species (64.2%) in both intertidal zone and subtidal zone. The number of species concentrates on some genera (Halimeda: 10 species; Caulerpa: 10 species; Codium: 6 species,...), they belong to Codiacea, Siphonales. There are some genera with only 1 species (Tydemania, Anadyomene, Microdictyon,...).